2022
DOI: 10.3389/fphar.2022.862539
|View full text |Cite
|
Sign up to set email alerts
|

Yokukansan Inhibits the Development of Morphine Tolerance by Regulating Presynaptic Proteins in DRG Neurons

Abstract: Opioids, such as morphine, are used in clinical settings for the management of acute and chronic pain. However, long-term use of morphine leads to antinociceptive tolerance and hypersensitivity. The cellular and molecular mechanisms of morphine tolerance seem to be quite complex, with suggestions including internalization of the μ-opioid receptor (MOR), neuroinflammation with activation of microglia and astrocytes, and changes in synaptic function in the central nervous system. Yokukansan (YKS), a traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…BoNT/A cleaves synaptosomal-associated protein-25 (SNAP-25), a key component of the SNARE complex [ 30 ]. We previously demonstrated that YKS inhibited neurotransmitter release by suppressing the overexpression of SNAP-25 [ 15 ]. This led us to speculate that YKS may share a mechanism of action like that of BoNTs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BoNT/A cleaves synaptosomal-associated protein-25 (SNAP-25), a key component of the SNARE complex [ 30 ]. We previously demonstrated that YKS inhibited neurotransmitter release by suppressing the overexpression of SNAP-25 [ 15 ]. This led us to speculate that YKS may share a mechanism of action like that of BoNTs.…”
Section: Discussionmentioning
confidence: 99%
“…YKS is a multi-component drug with multiple pharmacological actions [15][16][17][18]. Previous studies have reported its mechanisms of action, including inhibition of glutamate secretion [15], promotion of glutamate uptake by astrocytes [22], antagonism of glutamate N-methyl-D-aspartate (NMDA) receptors [23], agonistic effects on GABA A and 5-HT 1A receptors that inhibit neurotransmission [24,25], and antioxidant properties [26]. In a previous study using the HIC model animal, we reported the involvement of the antioxidant activity [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to investigate the efficacy of yokukansan in alleviating pain and psychiatric symptoms in patients with cancer undergoing treatment. Yokukansan has inhibitory effects on neuropathic pain and opioid analgesic tolerance in animal experiments and has been reported to improve irritability and sleep disorders in cancer patients [4][5][6]. Although there are reports of its analgesic effects in basic research and case studies, clinical studies validating these effects are scarce.…”
Section: Bridging Basic and Clinical Researchmentioning
confidence: 99%